The Massachusetts General Hospital Pulmonary Embolism Response Team (MGH PERT): Creation of a Multidisciplinary Program to Improve Care of Patients With Massive and Submassive Pulmonary Embolism. Issue 1 (February 2014) - Provias, Tim; Dudzinski, David M; Jaff, Michael R; Rosenfield, Kenneth; Channick, Richard; Baker, Joshua; Weinberg, Ido; Donaldson, Cameron; Narayan, Rajeev; Rassi, Andrew N; Kabrhel, Christopher
Abstract : : New and innovative tools have emerged for the treatment of massive and submassive pulmonary embolism (PE). These novel treatments, when considered alongside existing therapy, such as anticoagulation, systemic intravenous thrombolysis, and open surgical pulmonary embolectomy, have the potential to improve patient outcomes. However, data comparing different treatment modalities are sparse, and guidelines provide only general advice for their use. Treatment decisions rest on clinician expertise and institutional resources. Because various medical and surgical specialties offer different perspectives and expertise, a multidisciplinary approach to patients with massive and submassive PE is required. To address this need, we created a novel multidisciplinary program – the Massachusetts General Hospital (MGH) Pulmonary Embolism Response Team (PERT) – which brings together multiple specialists to rapidly evaluate intermediate- and high-risk patients with PE, formulate a treatment plan, and mobilize the necessary resources to provide the highest level of care. Development of a clinical, educational, and research infrastructure, as well as the creation of a national PERT consortium, will make our experience available to other institutions and serve as a platform for future studies to improve the care of complex patients with massive and submassive PE.